Review of intercultural academic and social challenges among Chinese international students in Malaysia - Kaur Mehar Singh, Manjet; Xue, Wenou (Journal of International Students, 2025)
International education is a current phenomenon characterized by an influx of international students from multiple countries into Malaysian universities. The highest number of international students at Malaysian universities is from China. The growth in the number of international students has led to an increasing diversity of cultural practices in the learning context, which requires intercultural adaptability. This review focused on the intercultural academic and social challenges faced by Chinese international students in Malaysian higher education institutions. Peer-reviewed articles published on Scopus, Taylor & Francis, EBSCO Host, Web of Science, Springer, PubMed, Google Scholar, and Wiley Online platforms over 10 years (2015-2025) were used for data collection. The Model of Intercultural Competence guided the review. The insights from the review offer opportunities for relevant stakeholders to create a framework that improves intercultural adaptability and sustainability among international students, specifically Chinese international students.